2023
DOI: 10.3389/fphar.2023.1038039
|View full text |Cite|
|
Sign up to set email alerts
|

Water extract of cacumen platycladi promotes hair growth through the Akt/GSK3β/β-catenin signaling pathway

Abstract: Cacumen Platycladi (CP) consists of the dried needles of Platycladus orientalis L.) Franco. It was clinically demonstrated that it effectively regenerates hair, but the underlying mechanism remains unknown. Thus, we employed shaved mice to verify the hair growth-promoting capability of the water extract of Cacumen Platycladi (WECP). The morphological and histological analyses revealed that WECP application could significantly promote hair growth and hair follicles (HFs) construction, in comparison to that of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Western blotting was performed as previously described 17 to examine changes in protein content and/or phosphorylation. Briefly, after designated treatments, cells were lysed and centrifuged to obtain protein samples.…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed as previously described 17 to examine changes in protein content and/or phosphorylation. Briefly, after designated treatments, cells were lysed and centrifuged to obtain protein samples.…”
Section: Methodsmentioning
confidence: 99%
“…14 Fu et al observed that rutin, myricetin, quercetin and isoquercitrin are main components in the water extract of CP by UPLC-Q/ TOF-MS in positive and negative ion modes. 13 We investigated changes in the phenolic contents of the different metabolites before and after fermentation using LC-MS (Table 3). Our results showed that the contents of homovanillic acid, protocatechuic acid, sinapinic acid, naringenin, eriodictyol, apigenin, and gallic acid significantly increased after fermentation, whereas those of ferulic acid, syringic acid, 4coumaric acid, and apigetrin decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Grouping. The anesthetized C57BL/6 mice (male, age 6 weeks, 20 ± 2 g) were then shaved with a clipper (Codos; Wuxi, China), denuded with depilatory cream (Veet, Shanghai, China), and randomly divided into five groups (n = 12), namely, control (saline), Fin (10 mg/kg finasteride), NF (160 mg/kg CPE 13 ), Pos (160 mg/kg FCP by L. plantarum CCFM1348), and Syn (160 mg/kg CPE and 5 × 10 9 cfu/mL of L. plantarum CCFM1348 live bacteria). All mice were administered respective treatments daily for 21 days.…”
Section: Hair Loss Mice Model Establishment and Trialmentioning
confidence: 99%
See 1 more Smart Citation
“…Network pharmacology is a new field that combines computer science and systems biology to study the mechanism of drug action and the molecular design of multi-target drugs [10]. It focuses on the study of “drug-disease-target gene” interaction networks at a systemic and comprehensive level.…”
Section: Introductionmentioning
confidence: 99%